The Effect of Time, pH, and Starter Concentration on Bioethanol Content in the Tobacco Stem Fermentation Process - Della Ainurrohma; Indah Wahyuningtyas; Putri Ayu Salsabila (University of Jember, 2024)
The depletion of fossil fuels is occurring in various parts of the world while fuel energy needs continue to increase. This condition encourages the search for alternative fuels with high availability of raw materials. Bioethanol, an environmentally friendly renewable energy from biomass, can be a solution to replace fuel oil. Tobacco stems, with high cellulose and hemicellulose content, can be used as raw materials for bioethanol. This study aims to optimize bioethanol production from tobacco stems through the influence of fermentation time, pH, and starter concentration. The research method involves base pretreatment, hydrolysis, fermentation, and distillation, with the results analyzed using the Response Surface Methodology (RSM) approach and the Central Composite Design (CCD) model. The independent variables used during fermentation include fermentation time (72 – 168 hours), pH (4 – 5), and starter concentration (0.1% – 0.3% w/v). Based on the Analysis of Variance (ANOVA), the variables that significantly affect ethanol content are fermentation time and starter concentration. The results of the CCD analysis showed optimum conditions at a fermentation time of 120 hours, pH 4.5, and starter concentration of 0.2% (w/v), producing a bioethanol content of 23.007% (v/v). This study shows the potential of tobacco stems as a sustainable source of bioethanol.